Math, asked by mondalmamata9874, 10 months ago

(√6+√10 - √21-√35)(√6-√10 + √21-√35)​

Answers

Answered by ishaan45modgil
0

SOLVING STEPS picture is above

click on above written equation

(√6+√10 - √21-√35)(√6-√10 + √21-√35)

=10

Attachments:
Answered by akhileshkumarsimri
1

Step-by-step explanation:

(√6+√10-√21-√35)(√6-√10+√21-√35)

= {√2(√3+√5) -√7(√3+√5) } {√2(√3-√5)+√7(√3-√7) }

={(√3+5)(√2-√7)} {(√3-√5)(√2+√7)}

=(√3+√5)(√3-√5)(√2-√7)(√2+√7)

= {(√3)²-(√5)²} {(√2)²-(√7)²}

=(3-5)(2-7)

=(-2)×(-5)

=+10

will be your answer

tumi ki west Bengle e thaako????

if u r satisfied with the answer

mark the answer as brainliest and thank me...

thank u...

Similar questions